Sorry, I don't speak French confronting the Canadian crisis that won't go away - Fraser, Graham 1946- (McClelland & Stewart, 2006)
As the threat of another Quebec referendum on independence looms, this book becomes important for every Canadian ' especially as language remains both a barrier and a bridge in our divided country Canada's language policy is the only connection between two largely unilingual societies ' English-speaking Canada and French-speaking Quebec. The country's success in staying together depends on making it work. How well is it working' Graham Fraser, an English-speaking Canadian who became bilingual, decided to take a clear-eyed look at the situation. The results are startling ' a blend of good news and bad. The Official Languages Act was passed with the support of every party in the House way back in 1969 ' yet Canada's language policy is still a controversial, red-hot topic; jobs, ideals, and ultimately the country are at stake. And the myth that the whole thing was always a plot to get francophones top jobs continues to live. Graham Fraser looks at the intentions, the hopes, the fears, the record, the myths, and the unexpected reality of a country that is still grappling with the language challenge that has shaped its history. He finds a paradox: after letting Quebec lawyers run the country for three decades, Canadians keep hoping the next generation will be bilingual ' but forty years after learning that the country faced a language crisis, Canada's universities still treat French as a foreign language. He describes the impact of language on politics and government (not to mention social life in Montreal and Ottawa) in a hard-hitting book that will be discussed everywhere, including the headlines in both languages.